Application Of Relay Feedback Method For Sliding Mode Control On Buck Converter System - Yusril Fatahilmi; Muhammad Aziz Muslim; Shiang-Hwua Yu (Jurnal Mahasiswa TEUB, 2020)
Abstract — The Power Electronic Converters (PEC) system is used in the modeling of switching power converters that have various control methodologies including linear control and non-linear control. One of the PEC systems is the Buck Converter which has the main task of controlling the output voltage / load. Buck Converter has the main problem in switching control. Switch control on Buck Converter uses high frequency which can damage components and MOSFET switch on Buck Converter. The voltage regulation of a DC - DC switching converter based on Pulse Width Modulation (PWM) that uses frequency domain control techniques and uses a small average converter signal model. The switching process that uses high frequency produces chattering which results in instability in the system. This paper presents modified sliding mode controller by testing the Relay Feedback control system in the application of Sliding Mode Control (SMC) to improve the performance of the Buck Converter control response. An analysis and simulation by schematic diagram of relay feedback was performed in this work. The purpose is to find the best control parameter by design of relay feedback. Research results shown that proposed work has good performance according to the pre-determined control specifications.   Keywords—buck converter; sliding mode control; pulse width modulation; relay feedback